GPIHBP1 on oligodendrocytes binds lipoprotein lipase within the human brain - Minjun Liu; Madison Hung; Ellen Kozlov; Megan Hung; Mariana Colaço-Gaspar; Shristi Roy; Yiping Tu; Shino D. Magaki; Christopher K. Williams; Maarja Andaloussi Mäe; Erik C. B. Johnson; Robert W. Siegel; et al. (Proceedings of the National Academy of Sciences, 2026)
In peripheral tissues, lipoprotein lipase (LPL) is secreted by parenchymal cells (adipocytes, myocytes) into the interstitial spaces, where it is captured by GPIHBP1 (a glycosylphosphatidylinositol-anchored protein of capillary endothelial cells) and escorted to the luminal surface of capillaries. The LPL inside capillaries hydrolyzes glycerolipids in the plasma lipoproteins, releasing fatty acids for parenchymal cells. In the central nervous system, LPL is synthesized by multiple cell types [e.g., microglia, oligodendrocyte precursor cells (OPCs)] and secreted into the interstitium, but a binding site for the LPL has never been identified. By examining single nuclei RNA-seq databases of the human brain, we found that GPIHBP1 is expressed by oligodendrocytes but not by OPCs. This gene-expression profile (high in oligodendrocytes, low in OPCs) is also observed in genes for myelin structural proteins, fatty acid binding and transport proteins, and lipid biosynthetic enzymes. GPIHBP1 expression in oligodendrocytes was confirmed by in situ hybridization studies of human brain and by immunohistochemical staining. Of note, GPIHBP1 and LPL are colocalized on oligodendrocytes in the human brain. Our findings identify GPIHBP1 as a principal binding site for interstitial LPL in the human brain and suggest that GPIHBP1-bound LPL could hydrolyze interstitial lipids and thereby supply oligodendrocytes with fatty acid nutrients.